Getting started with Google BERT : build and train state-of-the-art natural language processing models using BERT - Ravichandiran, Sudharsan (Packt Publishing Ltd., 2021)
Getting Started with Google BERT will help you become well-versed with the BERT model from scratch and learn how to create interesting NLP applications. You'll understand several variants of BERT such as ALBERT, RoBERTa, DistilBERT, ELECTRA, VideoBERT, and many others in detail.